Peningkatan Hasil Belajar PAI melalui Penerapan Index Card Match dengan Materi Zakat pada Siswa Kelas VI SD 4 Negeri Tenggeles - Putri, Mutiara Ananda; Sabila, Mujahidah Salimatus; Putri, Erika Wisni; Hanik, Elya Umi (ARZUSIN, 2021)
This Classroom Action Research is entitled "Improving PAI Learning Outcomes Through the Application of the Index Card Match Method with Zakat Materials for Class VI SDN 4 Tenggeles". The purpose of this study was to improve student learning outcomes with the Index Card Match method in Islamic Islamic Education learning with Zakat material. The research was conducted at SD Negeri 4 Tenggeles for 1 week, in November on 20 grade VI students. Data collection tools in this study were using student worksheets and tests for data on student learning outcomes. Data collection techniques using observation and test methods. The result of the analysis showed that for pre-cycle was 5%, the average and in the first cycle was 100%. From the results obtained, it is concluded that the application of the Index Card Match method can improve student learning outcomes in PAI learning the meaning of the final day in class VI SDN 4 Tenggeles is very satisfying.